Photocatalytic, electrocatalytic and photoelectrocatalytic degradation of pharmaceuticals in aqueous media: Analytical methods, mechanisms, simulations, catalysts and reactors. (1st April 2022) - Marinho, Belisa A.; Suhadolnik, Luka; Likozar, Blaž; Huš, Matej; Marinko, Živa; Čeh, Miran
Abstract: Pharmaceuticals are used every day in most parts of the world and great proportions of these substances are excreted unaltered or as active sub-products, posing a threat of pollution. To protect the aquatic ecosystems, innovative solutions such as photocatalysis, electrocatalysis and photoelectrocatalysis are required. In this article we provide a comprehensive review of photo- and electrocatalytic techniques for the removal of pharmaceuticals from water and wastewaters. The analytical and toxicity methods commonly used to study the degradation of pharmaceuticals are presented, and it is pointed high performance liquid chromatography analysis as the most common analytical method to evaluate the efficiency in the pharmaceutical's degradation. However, it is also highlighted that the evaluation of the toxicity is fundamental to ensure adequate treatment. The determination of the reactive species and the mechanistic evaluation of pharmaceuticals degradation are essential to understanding and enhancing the degradation process. A deep discussion of photocatalysis, electrocatalysis and photoelectrocatalysis principles and practical examples of their application in pharmaceuticals treatment is presented. The catalytic materials and the reactors used in these processes for the removal of pollutants are reviewed focusing on some representative examples. The reusability of catalysts is still restricted to a few reuse cycles. It was observed very limited results in the treatment of larger amounts of effluent and a lack of information about process costs, which were correlated to the difficulty of application of these techniques on real scale. Finally, the main advantages of photocatalysis, electrocatalysis and photoelectrocatalysis as high efficiency on pharmaceuticals degradation, and the main drawbacks, as the low quantum efficiency and/or high energetic consume are pointed out along with alternatives to overcome these limitations. Graphical abstract: Image 1 Highlights: Pharmaceuticals can be successfully degraded by PC, EC and PEC. To find a catalyst with good response in visible light, low recombination rate and low cost is a challenge. High energy consumption is still a major issue for pharmaceuticals' degradation by EC. Theoretical modeling of PC, EC and PEC from first principles remains limited to small molecules. Design of innovative reactors are necessary for pharmaceuticals' degradation on larger scale.